Optimal bounds from below of the critical load for elastic solids subject to uniaxial compression. Issue 1 (21st October 2015) - Castellano, Anna; Foti, Pilade; Fraddosio, Aguinaldo; Marzano, Salvatore; Piccioni, Mario Daniele
Abstract: In the recent papers [1, 2] we studied a new procedure based on the Korn inequality for determining sufficient conditions for the Hadamard stability, aimed at determining optimal lower bound estimates for the critical load in bifurcation problems. Here, we discuss the effectiveness of our approach for the classical representative problem of uniaxial compression of a Mooney‐Rivlin circular cylinder. We find that our lower bound estimate is effective and advantageous for applications, since it is easily implementable in numerical codes. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)